2015
DOI: 10.1104/pp.15.00706
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Contact Mode Atomic Force Microscopy in Aqueous Medium for Structural Analysis of Spinach Photosynthetic Complexes

Abstract: To investigate the dynamics of photosynthetic pigment-protein complexes in vascular plants at high resolution in an aqueous environment, membrane-protruding oxygen-evolving complexes (OECs) associated with photosystem II (PSII) on spinach (Spinacia oleracea) grana membranes were examined using contact mode atomic force microscopy. This study represents, to our knowledge, the first use of atomic force microscopy to distinguish the putative large extrinsic loop of Photosystem II CP47 reaction center protein (CP4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 73 publications
5
18
0
Order By: Relevance
“…The trimodal nearest-neighbour distribution of PSII in SI (Fig. 3G, blue arrows) is in agreement with the organization of PSII observed in AFM images of grana membranes in SI (7, 43, 65) as is the more disordered arrangement in SII (23, 56). Despite the increase in the number of LHCII and PSI-LHCII complexes in the stromal lamellae in SII compared to SI, PSI nearest-neighbour distributions were indistinguishable (Fig.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The trimodal nearest-neighbour distribution of PSII in SI (Fig. 3G, blue arrows) is in agreement with the organization of PSII observed in AFM images of grana membranes in SI (7, 43, 65) as is the more disordered arrangement in SII (23, 56). Despite the increase in the number of LHCII and PSI-LHCII complexes in the stromal lamellae in SII compared to SI, PSI nearest-neighbour distributions were indistinguishable (Fig.…”
Section: Resultssupporting
confidence: 87%
“…Given the unanswered questions that remain on the precise mechanism of state transitions new approaches are needed to clarify how the altered balance of forces upon LHCII phosphorylation affect the thylakoid macro-organization. The structural model of the thylakoid membrane at the individual protein complex level presented here was made possible by recent breakthroughs in elucidating thylakoid organization and dynamics using in atomic force microscopy (AFM) (7, 23, 43) and structured illumination microscopy (SIM) (31, 44), and publication of high-resolution structures of the key protein complexes involved in the light reactions (4550). Recently developed algorithms, which made the calculation of whether two or more particles spatially overlap tractable, were also essential (see methods).…”
Section: Introductionmentioning
confidence: 99%
“…These analyses showed that the neighbors of PSI are likely to be PSII, as depicted in Figure 5D. The pronounced topology of the PSII water-oxidizing complex on the lumenal side of the membrane aids its identification in AFM topographs of plant thylakoids (Sznee et al, 2011;Johnson et al, 2014;Kirchhoff et al, 2008;Phuthong et al, 2015), but in our measurements, this side of the membrane adheres to the mica support and is not available for imaging. Figure 6 shows that, using a different method to immobilize membranes, PSII complexes can be imaged at low resolution, and they likely sit alongside PSI complexes.…”
Section: Discussionmentioning
confidence: 90%
“…However, their structural state in the native membrane environment and their collective dynamic rearrangements reflecting the physiologically crucial processes of acclimation and adaptation of the photosynthetic apparatus to environmental factors have only recently started to emerge. Atomic force microscopy (AFM) of spinach (Spinacia oleracea) membranes enriched in PSII, reported here by Phuthong et al (2015), is currently one of only a few studies that aims at visualizing the photosynthetic membrane proteins at high resolution (a few nanometers) in an environment close to the native one: unfrozen and aquatic (Sznee et al, 2011;Johnson et al, 2014). Unlike freeze-fracture, negative staining, or cryoelectron microscopy, AFM possesses an enormous potential for the visualization of selected membrane components using the principles of natural proteincofactor or protein-protein interactions (Johnson et al, 2014).…”
mentioning
confidence: 99%
“…Unlike freeze-fracture, negative staining, or cryoelectron microscopy, AFM possesses an enormous potential for the visualization of selected membrane components using the principles of natural proteincofactor or protein-protein interactions (Johnson et al, 2014). Phuthong et al (2015) report a high-resolution topography of the lumen-protruding domains of key components of the PSII reaction center: inner antenna chlorophyll proteins, CP43 and CP47, and extrinsic subunits, PsbO/PsbP/PsbQ, involved in oxygen evolution, offering a great potential for monitoring the conformational changes associated with oxygen evolution and related adaptive changes in the complex. In addition, the authors identified a new type of particle protruding on the stromal site of the membrane that is likely to be granal PSI.…”
mentioning
confidence: 99%